High-sensitive Troponin T is not associated with the progression of asymptomatic mild to moderate aortic stenosis: a post hoc substudy of the SEAS trial. (3rd October 2022) - Hadziselimovic, E; Greve, A M; Sajadieh, A; Olsen, M H; Kesaniemi, Y A; Nienaber, C A; Ray, S G; Rossebo, A B; Willenheimer, R; Wachtell, K; Nielsen, O W
Abstract: Background: Aortic stenosis (AS) and coronary artery disease (CAD) share pathophysiological pathways, as reflected by frequent concomitant revascularization in patients undergoing aortic valve replacement (AVR). High-sensitive Troponin T (hsTnT) is a proven biomarker of cardiomyocyte overload and injury, and predicts postoperative mortality after AVR. However, it is unknown if hsTnT can predict AVR, mortality or ischemic coronary events (ICE) in asymptomatic AS patients. Purpose: To investigate the hypothesis that increased hsTnT is associated with more severe AS and a higher risk of adverse outcomes in asymptomatic AS patients without overt CAD. Methods: hsTnT concentrations were examined at baseline and after 1-year follow-up in 1739 asymptomatic AS patients enrolled in the randomized, double-blind Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) study. The main inclusion criteria were: left ventricular (LV) ejection fraction >55%, transaortic maximal velocity between 2.5–4.0 m/s, and no history of CAD. The primary exposure variable was increased hsTnT (>14 pg/mL according to the assay manufacturer, Roche). This study's primary endpoint was a composite of competing risk outcomes: all-cause mortality as the first event, AVR without revascularization, and ICE (defined as myocardial infarction before AVR, PCI before or combined with AVR, or any CABG). Multivariable regression examined associations between hsTnT and clinical variables. Cox proportional hazards regression models were adjusted for age, sex, creatinine, LV mass index, mean aortic pressure gradient (Pmean) and stratified by center and lipid-lowering treatment. We analyzed outcomes during 5-year follow-up from baseline. Results: At baseline, 453 (26.0%) patients had increased hsTnT and 302 (17.4%) had moderate-severe AS with a mean (SD) aortic valve area of 0.8 (0.2) cm 2 and Pmean of 33.2 (8.8) mmHg. The median annual hsTnT change from baseline to year 1 was 0.8 pg/mL (IQR, −0.4 to 2.3), regardless of AS severity (P=0.08). In adjusted models, log(hsTnT at baseline) was associated with age, sex, creatinine, and LV mass index (all P<0.05), but not with AS severity (P=0.36). The incidence rate ratio for ICE (Figure 1) in patients with increased vs normal baseline hsTnT concentrations was 2.32 (95% CI, 1.72–3.11, P<0.001). In adjusted Cox regression, increased hsTnT was associated with an increased 5-year ICE risk (HR 1.64; 95% CI, 1.18–2.29, P=0.003), but neither with AVR without revascularization nor death (Figure 1). Conclusion: In these asymptomatic AS patients without overt CAD, hsTnT is often normal and remains stable during 1 year of follow-up regardless of AS severity. Increased hsTnT is associated with CAD-related events, but neither to AS severity nor AVR without concomitant revascularization. This analysis does not support routine hsTnT measurement in asymptomatic AS to predict AVR related to AS progression, although hsTnT could improve the risk assessment for ICE. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Main sponsor (SEAS): Merck & Co Inc, Whitehouse Station, New JerseyBlood analysis sponsor: Roche Diagnostics International Ltd, Switzerland